Photovoltaic panel, preparation method thereof and photovoltaic module comprising photovoltaic panel
Through the combination of nanocellulose-based flame retardant and methyl methacrylate and other additives, the problems of low light transmittance, poor fire resistance and insufficient mechanical properties of lightweight photovoltaic modules are solved, and high light transmittance and Photovoltaic panels with good flame retardant performance are suitable for building roofs and other scenarios.
Patent Information
- Application Number
- CN202411192622.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-01-14
AI Technical Summary
The existing lightweight photovoltaic modules have low light transmittance, poor fire resistance, insufficient mechanical properties and environmental pollution problems, which limit their use in integrated construction applications.
Using nanocellulose-based flame retardant, nanocellulose is grafted through phosphate group-containing organic acids and melamine or its derivatives, combined with methyl methacrylate, to prepare excellent light transmittance, improved flame retardant and resistance Photovoltaic sheets with thermal, wear and ultraviolet resistance, and initiators, anti-hydrolytics and scratch resistant agents are added to improve overall performance.
It has achieved high light transmittance, good flame retardant performance, improved mechanical properties and environmental friendliness of lightweight photovoltaic panels, which has broadened its application in scenarios such as building roofs, especially in terms of fire resistance and durability.
Smart Images

Figure CN119306891A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of photovoltaic materials, and specifically, relates to a photovoltaic panel, a preparation method thereof, and a photovoltaic module including the photovoltaic panel. Background Art
[0002] In recent years, with the enhancement of people's environmental awareness and the country's emphasis on environmental protection, clean energy such as photovoltaics has developed rapidly. At present, the photovoltaic modules on the market are still mainly double-glass modules and single-glass modules. Due to the thicker glass used, the weight of the entire module is too high, and the glass also has disadvantages such as easy breakage, which limits its use in specific occasions such as photovoltaic building integration (BIPV). In addition, there is also a kind of lightweight photovoltaic module commonly used in this industry, which uses polymer materials instead of glass as the front and back panels of the module. It is lighter in weight and is widely used in projects with low loads such as color steel tile roofs.
[0003] At present, the front panels of lightweight photovoltaic modules on the market are mostly made of polyethylene terephthalate (PET) film materials, and the back panels are glass fiber composite materials. Such lightweight modules have poor hail resistance, and the glass fiber back panel materials have low light transmittance or are opaque, and do not have the ability to generate electricity on both sides. In addition, lightweight modules are mostly used on building roofs, which puts certain requirements on the fire resistance of the modules. However, most of the existing lightweight modules do not consider fire resistance too much, which poses a great safety hazard during use. Even if some lightweight modules have considered fire resistance, the fire resistance is poor. In addition, some people use halogen-containing front and back panel materials. Although such panels have flame retardant effects, they will release harmful gases when burned, polluting the environment and not meeting environmental protection requirements.
[0004] Therefore, there is an urgent need to develop an environmentally friendly lightweight photovoltaic panel with excellent light transmittance, improved flame retardancy and mechanical properties. Summary of the invention
[0005] In view of this, the present application provides an environmentally friendly photovoltaic panel which not only has excellent light transmittance but also has improved flame retardant properties, as well as improved other properties such as heat resistance, wear resistance and UV resistance, a method for preparing the photovoltaic panel, and a photovoltaic module including the photovoltaic panel.
[0006] Specifically, according to the first aspect of the present application, a photovoltaic panel is provided, wherein the raw materials for preparing the photovoltaic panel include: methyl methacrylate, nanocellulose-based flame retardant, and the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or its derivatives.
[0007] In this embodiment, the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or its derivatives. It can be seen that the nanocellulose-based flame retardant is a novel flame retardant that integrates an acid source, a gas source and a carbon source, wherein an organic acid containing a phosphoric acid group is used as an acid source, melamine or its derivatives are used as a gas source, and nanocellulose is used as a carbon source. When the polymer matrix is heated and burned, the three act synergistically, which can not only hinder the contact of heat and combustible gas with the polymer matrix, but also dilute the combustible gas, and inhibit heat and combustible gas from entering the interior of the polymer matrix, thereby achieving the purpose of flame retardancy from all aspects. In addition, the nanocellulose-based flame retardant belongs to a bio-based flame retardant, does not contain halogen, and is an environmentally friendly flame retardant.
[0008] In addition, since the nanocellulose-based flame retardant is a nanometer-sized cellulose particle, it is easy to disperse in a polymethyl methacrylate (PMMA) matrix, so it is introduced into the PMMA polymer matrix to further improve the mechanical properties of the polymer matrix as a reinforcement. Furthermore, the introduction of nanometer-sized cellulose-based flame retardants into the PMMA matrix can form a cross-linked network, which makes it difficult for the molecular weight chains inside the PMMA to move, thereby improving its heat resistance.
[0009] In summary, using the above-mentioned nanocellulose-based flame retardant and methyl methacrylate together in photovoltaic panels can not only make the photovoltaic panels have excellent flame retardant properties, but also improve the mechanical properties and heat resistance of the photovoltaic panels, and is environmentally friendly.
[0010] In some embodiments, the raw materials for preparing the photovoltaic panel further include: an initiator, an anti-hydrolysis agent, an ultraviolet absorber, and / or an anti-scratch agent.
[0011] In this embodiment, the initiator can cross-link and polymerize the methyl methacrylate monomer into a polymethyl methacrylate structure, thereby forming a substrate for the photovoltaic panel; the anti-hydrolysis agent can effectively prevent the resin from hydrolyzing and improve the panel's resistance to water vapor erosion; the ultraviolet absorber can effectively absorb or scatter ultraviolet rays and reduce direct damage to the photovoltaic module, thereby protecting the performance of the photovoltaic module and extending its service life; the anti-scratch agent can significantly improve the wear resistance and scratch resistance of the PMMA matrix.
[0012] In some embodiments, the raw materials for preparing the photovoltaic panel include, by weight: 75-95 parts of the methyl methacrylate, 1-10 parts of the nanocellulose-based flame retardant, 0.5-2 parts of the ultraviolet absorber, 1-5 parts of the scratch resistant agent, 1-3 parts of the initiator, and 0.5-5 parts of the anti-hydrolysis agent.
[0013] In this embodiment, the above-mentioned ratio can give full play to the performance advantages of methyl methacrylate and nanocellulose-based flame retardants, so that the photovoltaic panel produced by cross-linking and curing is not only light in weight and high in light transmittance, but also has good flame retardancy, impact resistance, heat resistance, wear resistance, and UV resistance, and its comprehensive performance is more excellent.
[0014] In some embodiments, the degree of substitution of the nanocellulose-based flame retardant is 30%-70%.
[0015] In this embodiment, the degree of substitution is controlled to be 30%-70%, which can achieve an optimal balance between flame retardant effect and ease of preparation.
[0016] In some embodiments, the organic acid containing a phosphoric acid group is phytic acid, and / or polyphosphoric acid.
[0017] In some embodiments, the nanocellulose-based flame retardant is nanocellulose grafted with phytic acid melamine, such as a combination of one or more of bacterial nanocellulose grafted with phytic acid melamine, microfiber nanocellulose grafted with phytic acid melamine and cellulose nanocrystal grafted with phytic acid melamine; preferably, the initiator is a combination of one or more of tert-butyl perbenzoate (TBPB), benzoyl peroxide (BPO) and azobisisobutyl cyanide (AIBN); preferably, the anti-hydrolysis agent is polycarbodiimide (PCD), isocyanates and Preferably, the ultraviolet absorber is a combination of one or more of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol (UV-571), 2-(2′-hydroxy-5′-methylphenyl)benzotriazole (UV-P), 2-(2′-hydroxy-3′, 5′-di-tert-pentylphenyl)benzotriazole (UV-328) and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol (UV-1577); Preferably, the scratch resistant agent is an organic compound containing a polysiloxane molecular chain and an unsaturated bond, preferably, the molecular weight of the scratch resistant agent is 2000-10000, preferably, the scratch resistant agent is vinyl polydimethylsiloxane (PDSV).
[0018] In this embodiment, the scratch resistant agent contains both polysiloxane molecular chains and unsaturated bonds, wherein the surface tension of the polysiloxane molecular chains is relatively low, and thus the friction coefficient of the PMMA surface can be effectively reduced, thereby improving the wear resistance and scratch resistance of PMMA. In addition, since it also contains unsaturated bonds, when the free radical initiator initiates curing, the substance can form a cross-linked network structure with MMA, thereby enhancing the rigidity of PMMA and further improving the wear resistance of PMMA.
[0019] In this embodiment, the molecular weight of the scratch resistant agent is controlled to be 2000-10000, which can not only achieve a good scratch resistant effect but also have a moderate viscosity.
[0020] In addition, the above-mentioned new flame-retardant photovoltaic panels provided in this application can be used as lightweight flexible component packaging materials to improve the fire resistance of the components. They can be directly applied to the roofs of old factories, color steel tiles and other buildings, broadening the application scenarios of photovoltaic components.
[0021] According to the second aspect of the present application, a method for preparing the photovoltaic panel described in the first aspect of the present application is provided, wherein the method comprises: 1) adding a nanocellulose-based flame retardant to methyl methacrylate or a mixture containing methyl methacrylate, and mixing them evenly, wherein the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or its derivatives; 2) degassing the mixture obtained in step 1), and curing it to obtain the photovoltaic panel.
[0022] It can be seen that the preparation method of the photovoltaic panel provided in the present application is simple to operate and is easy to industrialize.
[0023] In some embodiments, the mixture comprising methyl methacrylate further comprises: an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber.
[0024] In some embodiments, in step 1), after the nanocellulose-based flame retardant is added to methyl methacrylate and mixed evenly, an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber are added and mixed evenly.
[0025] In some embodiments, the nanocellulose-based flame retardant is obtained by first reacting the nanocellulose with the organic acid containing a phosphoric acid group, and then reacting with the melamine or a derivative thereof.
[0026] According to the third aspect of the present application, a photovoltaic module is provided, wherein the photovoltaic module includes a stacked front panel, solar cells and a back panel, the solar cells are located between the front panel and the back panel, and at least one of the front panel and the back panel is made of the photovoltaic panel according to the first aspect of the present application or the photovoltaic panel prepared by the method described in the second aspect of the present application.
[0027] The above-mentioned new flame-retardant photovoltaic panels are applied to the transparent front panels and transparent back panels of photovoltaic modules. While reducing the weight of the modules, it also takes into account the flame-retardant properties of the materials, thus broadening the application scenarios of photovoltaic modules.
[0028] In addition, photovoltaic panels are an important component of photovoltaic modules. Therefore, photovoltaic modules including the above-mentioned photovoltaic panels can achieve the same technical effects as photovoltaic panels, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other implementation plans can be obtained based on these drawings without paying creative work.
[0030] Figure 1 The structure of a photovoltaic panel according to some embodiments of the present application is schematically shown, wherein 11 is a resin material and 12 is nanocellulose-based flame retardant particles. DETAILED DESCRIPTION
[0031] The present application will be described clearly and completely below in conjunction with the embodiments and drawings of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. All other embodiments that can be obtained by a person of ordinary skill in the art based on the embodiments in the present application belong to the scope of protection of the present application.
[0032] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0033] As mentioned above, the lightweight photovoltaic modules currently on the market generally have problems such as low light transmittance, poor fire resistance, poor mechanical properties and environmental pollution. Therefore, there is an urgent need to develop a new type of photovoltaic panel to overcome the above problems in photovoltaic modules.
[0034] Therefore, the present application provides a photovoltaic panel, wherein the raw materials for preparing the photovoltaic panel include: methyl methacrylate, nanocellulose-based flame retardant, and the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or its derivatives.
[0035] In the photovoltaic panel provided in the present application, methyl methacrylate (MMA) can be polymerized into polymethyl methacrylate (PMMA), the matrix component of the photovoltaic panel. Polymethyl methacrylate as a matrix material can provide the photovoltaic panel with excellent transparency, outstanding aging resistance and chemical properties, good insulation, etc.
[0036] In the present application, the nanocellulose-based flame retardant refers to a cellulose-based flame retardant with a diameter in the nanometer range (i.e., 1-100 nm). For more specific sizes, the present application does not further limit them, and any size within the above range can be used in the present application.
[0037] In the above photovoltaic plate, the nanocellulose-based flame retardant is formed by grafting nanocellulose with organic acids containing phosphoric acid groups and melamine or its derivatives. The nanocellulose-based flame retardant is a new type of expansion flame retardant that integrates acid source, gas source and carbon source. The organic acid containing phosphoric acid groups as an acid source, because it contains a large amount of phosphorus elements, helps the polymethyl methacrylate (PMMA) polymer matrix to be dehydrated by heat to form a carbon layer when heated and burned, thereby hindering the contact of heat and combustible gas with PMMA; melamine or its derivatives as a gas source, when it is thermally decomposed, it will absorb a large amount of heat and produce a large amount of nitrogen-containing non-combustible gas to dilute the combustible gas, thereby achieving the purpose of flame retardancy; nanocellulose as a carbon source, under the synergistic effect of the organic acid containing phosphoric acid groups and melamine or its derivatives, when PMMA is heated and burned, a dense carbon source can be formed, which inhibits heat and oxygen from entering the polymer matrix, thereby achieving the purpose of flame retardancy.
[0038] In the present application, the organic acid containing a phosphoric acid group is an organic acid containing 4-8, for example 4, 5, 6, 7, 8 phosphoric acid groups, such as phytic acid and / or polyphosphoric acid. In some embodiments, the organic acid containing a phosphoric acid group is phytic acid.
[0039] In the present application, the melamine derivative refers to any derivative of melamine that can generate nitrogen-containing non-combustible gas after combustion, such as melamine phosphate.
[0040] As understood by those skilled in the art, the degree of substitution (DS) refers to the extent to which a certain group or atom in a molecule is replaced by other groups or atoms. In the present application, the degree of substitution of the nanocellulose-based flame retardant refers to the extent to which the hydroxyl group in the cellulose reacts with the phosphate group in the organic acid containing the phosphate group and is functionalized by the group. The degree of substitution can be determined by acid-base titration. Specifically, the nanocellulose-based flame retardant is added to deionized water to form a suspension of 2 mg / mL, and ultrasonically dispersed for 30 minutes, then an excess of 0.1 mol / L NaOH solution and 1 drop of phenolphthalein reagent are added thereto, and then titrated with 0.1 mol / L HCl solution, when the color of the solution changes from purple-red to colorless, the titration end point is reached.
[0041] Its DS can be calculated by the following formulas (1) and (2):
[0042]
[0043] Wherein B is the amount of NaOH added (mL); C is the concentration of NaOH (mol / L); D is the volume of HCl consumed by NaOH (mL); E is the concentration of HCl (mol / L); F is the mass of nanocellulose-based flame retardant (g); 162 is the molar mass of cellulose anhydroglucose unit (g / mol); 750 is the molar mass increased by nanocellulose-based flame retardant (g / mol).
[0044] In the present application, if the amount of nanocellulose grafted with an organic acid containing a phosphoric acid group and melamine or its derivatives is too small, the flame retardant effect cannot be achieved. Increasing the amount of grafting will produce better results, but it is very difficult. Therefore, in some embodiments, the degree of substitution of the nanocellulose-based flame retardant is 30%-70%, which can achieve the best balance between flame retardant effect and ease of preparation.
[0045] In some embodiments, the nanocellulose-based flame retardant is nanocellulose grafted with phytic acid and melamine. It can be understood that the nanocellulose-based flame retardant is formed by grafting nanocellulose with phytic acid and melamine.
[0046] In some embodiments, the nanocellulose-based flame retardant is a combination of one or more of bacterial nanocellulose grafted with phytic acid melamine, microfiber nanocellulose grafted with phytic acid melamine, and cellulose nanocrystal grafted with phytic acid melamine. It is understood that bacterial nanocellulose grafted with phytic acid melamine, microfiber nanocellulose grafted with phytic acid melamine, and cellulose nanocrystal grafted with phytic acid melamine are respectively formed by grafting bacterial nanocellulose, microfiber nanocellulose, and cellulose nanocrystals with phytic acid and melamine.
[0047] As understood by those skilled in the art, "bacterial nanocellulose" is a natural nano polymer synthesized by bacterial fermentation. "Microfiber nanocellulose" and "cellulose nanocrystal" are obtained by treating plant fibers by physical or chemical methods. In some embodiments, the diameter of microfiber nanocellulose is 5-60nm and the length is 1-9 μ m. In some embodiments, the diameter of cellulose nanocrystal is 5-70nm and the length is 100-250nm.
[0048] Figure 1 The structure of the photovoltaic panel according to some embodiments of the present application is schematically shown. It can be seen that the nanocellulose-based flame retardant particles 12 are uniformly dispersed in the resin material 11, wherein the resin material 11 is formed by curing a raw material containing methyl methacrylate at a high temperature.
[0049] In some embodiments, the raw materials for preparing the photovoltaic panel further include: an initiator, an anti-hydrolysis agent, an ultraviolet absorber, and / or an anti-scratch agent.
[0050] In some embodiments, the raw materials for preparing the photovoltaic panel include, by weight: 75-95 parts of the methyl methacrylate, 1-10 parts of the nanocellulose-based flame retardant, 0.5-2 parts of the ultraviolet absorber, 1-5 parts of the scratch resistant agent, 1-3 parts of the initiator, and 0.5-5 parts of the anti-hydrolysis agent.
[0051] It should be noted that, when the raw materials for preparing the photovoltaic panel do not include the above components at the same time, the components included are also present in the above weight parts. For example, in some embodiments, the raw materials for preparing the photovoltaic panel include, by weight parts: 75-95 parts of methyl methacrylate, 1-10 parts of nanocellulose-based flame retardant, 1-3 parts of initiator, and 0.5-5 parts of anti-hydrolysis agent.
[0052] In some embodiments, the raw materials for preparing the photovoltaic panel include, by weight: 80 parts of the methyl methacrylate, 10 parts of the nanocellulose-based flame retardant, 1.5 parts of the ultraviolet absorber, 5 parts of the scratch resistant agent, 2 parts of the initiator, and 1.5 parts of the anti-hydrolysis agent.
[0053] As understood by those skilled in the art, the initiator is easily decomposed into free radicals by heat, which can initiate free radical polymerization and copolymerization of olefins and dienes, thereby cross-linking and polymerizing methyl methacrylate monomers into polymethyl methacrylate. In some embodiments, the initiator is a combination of one or more of tert-butyl perbenzoate (TBPB), benzoyl peroxide (BPO) and azobisisobutyl cyanide (AIBN). Of course, other initiators known in the art that can be used in the present application can also be used, and the present application does not limit this.
[0054] In addition, since photovoltaic modules are generally used in outdoor environments, the addition of an anti-hydrolysis agent can effectively prevent the resin from hydrolyzing and improve the board's resistance to water vapor erosion. In some embodiments, the anti-hydrolysis agent is polycarbodiimide (PCD), isocyanate and A combination of one or more oxazoline compounds. Oxazoline compounds are 2- Of course, other anti-hydrolysis agents known in the art and applicable to the present application may also be used, and the present application does not limit this.
[0055] As mentioned above, photovoltaic modules are generally used in outdoor environments. The addition of ultraviolet absorbers can effectively absorb or scatter ultraviolet rays, reduce direct damage to photovoltaic modules, thereby protecting the performance of photovoltaic modules and extending their service life. In some embodiments, the ultraviolet absorber is a combination of one or more of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol (UV-571), 2-(2′-hydroxy-5′-methylphenyl) benzotriazole (UV-P), 2-(2′-hydroxy-3′, 5′-di-tert-pentylphenyl) benzotriazole (UV-328) and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol (UV-1577). Of course, other ultraviolet absorbers known in the art that can be used in the present application can also be used, and the present application is not limited to this.
[0056] In order to further improve the wear resistance and scratch resistance of the photovoltaic panel, a scratch resistant agent is also added. In some embodiments, the scratch resistant agent is an organic compound containing a polysiloxane molecular chain and an unsaturated bond, wherein the surface tension of the polysiloxane molecular chain is low, so it can effectively reduce the friction coefficient of the PMMA surface and improve the wear resistance and scratch resistance of PMMA. In addition, since it also contains unsaturated bonds such as unsaturated carbon-carbon double bonds, when the free radical initiator initiates curing, the substance can form a cross-linked network structure with MMA, which can enhance the rigidity of PMMA and further improve the wear resistance of PMMA.
[0057] In some embodiments, the molecular weight of the scratch resistant agent is 2000-10000, for example, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000. If the molecular weight is less than 2000, the scratch resistance effect is not ideal; if the molecular weight is greater than 10000, the viscosity of the scratch resistant agent will be too high and it will be difficult to disperse.
[0058] In some embodiments, the scratch resistant agent is vinyl polydimethylsiloxane (PDSV) or vinyl poly (dimethylsiloxane-CO-diphenylsiloxane). In some embodiments, the molecular weight of vinyl polydimethylsiloxane (PDSV) is 2000-10000. Of course, other scratch resistant agents known in the art that can be used in the present application can also be used, and the present application is not limited thereto.
[0059] The above-mentioned new flame-retardant photovoltaic panel provided in this application can be used as a lightweight flexible component packaging material, which greatly improves the fire resistance of the component. It can be directly applied to the roofs of old factories, color steel tiles and other buildings, broadening the application scenarios of photovoltaic components.
[0060] According to the second aspect of the present application, a method for preparing the photovoltaic panel according to the first aspect of the present application is also provided, wherein the method comprises:
[0061] 1) adding a nanocellulose-based flame retardant to methyl methacrylate or a mixture containing methyl methacrylate and mixing them uniformly, wherein the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or a derivative thereof;
[0062] 2) Degassing the mixture obtained in step 1) and curing it to obtain the photovoltaic panel.
[0063] It can be seen that the preparation method of the photovoltaic panel provided in the present application is simple to operate and is easy to industrialize.
[0064] In some embodiments, the mixture comprising methyl methacrylate further comprises: an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber.
[0065] In some embodiments, in step 1), after the nanocellulose-based flame retardant is added to methyl methacrylate and mixed evenly, an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber are added and mixed evenly.
[0066] In the present application, the numbering of the steps is only intended to facilitate the description of the method and is not intended to limit the order of execution of each step. That is to say, the above steps can be performed simultaneously or can be adjusted arbitrarily as needed. This application does not limit this and technical personnel in this field can make choices as needed.
[0067] In the above method, the weight proportions of the raw materials included in the preparation of the photovoltaic panel are 75-95 parts of the methyl methacrylate, 1-10 parts of the nanocellulose-based flame retardant, 0.5-2 parts of the ultraviolet absorber, 1-5 parts of the scratch-resistant agent, 1-3 parts of the initiator, and 0.5-5 parts of the anti-hydrolysis agent. It should be noted that when the raw materials for preparing the photovoltaic panel do not include the above components at the same time, the raw materials included are also present in the above weight proportions. For example, in some embodiments, the raw materials for preparing the photovoltaic panel include, by weight proportions: 75-95 parts of the methyl methacrylate, 1-10 parts of the nanocellulose-based flame retardant, 1-3 parts of the initiator, and 0.5-5 parts of the anti-hydrolysis agent.
[0068] In some embodiments, in step 1), the mixture may be uniformly mixed after stirring for 5-10 minutes using a stirring device.
[0069] In the above step 2), the mixture is degassed by vacuuming or the like, and then poured into a mold until the resin fills the entire mold, and then placed in an oven for curing. After curing and forming, the sheet is taken out of the mold to obtain the above-mentioned enhanced composite photovoltaic sheet.
[0070] In some embodiments, the curing temperature may be 80-120° C., and the curing time may be 1.5-3 hours.
[0071] In some embodiments, the curing process is divided into three stages. The curing temperature of the first stage is 80-100°C, for example, 90°C, and the curing time is 20-40min, for example, 25min; the curing temperature of the second stage is 50-70°C, for example, 60°C, and the curing time is 40-80min, for example, 60min; the curing temperature of the third stage is 100-120°C, for example, 120°C, and the curing time is 40-60min, for example, 60min.
[0072] In the present application, the nanocellulose-based flame retardant is obtained by first reacting the nanocellulose with the organic acid containing a phosphoric acid group, and then reacting with the melamine or its derivative. Specifically, the nanocellulose is dispersed in water, and then the organic acid containing a phosphoric acid group and an acid catalyst are added, the pH of the solution is adjusted to 3-4, and the reaction is carried out at 100-120°C, and then melamine or its derivative is added. After the reaction, the nanocellulose-based flame retardant is obtained.
[0073] In some embodiments, the mass ratio of nanocellulose: organic acid containing phosphoric acid group: melamine or its derivative is 1:(1-5):(1-5).
[0074] In some embodiments, the time required for the two reactions is independently 5-8 h.
[0075] In some embodiments, after the two reactions, a large amount of deionized water is used for washing for multiple times, for example, 10 times.
[0076] In some embodiments, the acidic catalyst may be at least one of sodium bisulfate monohydrate and p-toluenesulfonic acid.
[0077] In some embodiments, the nanocellulose is dispersed in water, and then a phytic acid aqueous solution is added, and an acidic catalyst is added, the pH value of the solution is adjusted to about 3-4, and the reaction is carried out at 100-120°C for 5-8 hours. After the reaction is completed, the solution is repeatedly centrifuged and washed 10 times with a large amount of deionized water; then the nanocellulose grafted with phytic acid is dispersed in water, an aqueous melamine solution is added, and the reaction is carried out at 100-120°C for 5-8 hours. After the reaction is completed, the solution is repeatedly centrifuged and washed 10 times with a large amount of deionized water, and freeze-dried to obtain a nanocellulose-based flame retardant.
[0078] In one embodiment, the method for preparing the photovoltaic panel described in the first aspect of the present application comprises:
[0079] 1) Preparation of nanocellulose-based flame retardant: nanocellulose is dispersed in water, then an organic acid containing a phosphoric acid group and an acid catalyst are added, the pH of the solution is adjusted to 3-4, and the reaction is carried out at 100-120° C., and then melamine or a derivative thereof is added. After the reaction, a nanocellulose-based flame retardant is obtained, and the mass ratio of nanocellulose: organic acid containing a phosphoric acid group: melamine or a derivative thereof is 1:(1-5):(1-5);
[0080] 2) adding 1-3 parts of an initiator, 0.5-5 parts of an anti-hydrolysis agent, 1-5 parts of a scratch-resistant agent, and / or 0.5-2 parts of an ultraviolet absorber to 75-95 parts of the methyl methacrylate, stirring and mixing uniformly;
[0081] 3) adding 1-10 parts of the nanocellulose-based flame retardant, stirring for 10 minutes, and mixing thoroughly to make it evenly dispersed;
[0082] 4) degassing the mixture obtained in step 3) by vacuuming or the like;
[0083] 5) After removing the bubbles, pour the mixture into the mold until the resin fills the entire mold, put it into the oven, and cure it at 80-120℃ for 1.5-3h;
[0084] 6) After curing and molding, the sheet is taken out from the mold to obtain a new flame-retardant and lightweight photovoltaic sheet.
[0085] According to the third aspect of the present application, a photovoltaic module is provided, wherein the photovoltaic module includes a stacked front panel, solar cells and a back panel, the solar cells are located between the front panel and the back panel, and at least one of the front panel and the back panel is made of the photovoltaic panel according to the first aspect of the present application or the photovoltaic panel prepared by the method described in the second aspect of the present application.
[0086] The new flame-retardant photovoltaic panel material provided in the present application is applied to the transparent front plate and transparent back plate of the photovoltaic module, which not only reduces the weight of the module, but also takes into account the flame retardant properties of the material, thereby broadening the application scenarios of the photovoltaic module.
[0087] In addition, photovoltaic panels are an important component of photovoltaic modules. Therefore, photovoltaic modules including the above-mentioned photovoltaic panels can achieve the same technical effects as photovoltaic panels, which will not be repeated here.
[0088] The present invention is described in more detail below in conjunction with the examples, which are only preferred embodiments of the present invention and are not intended to limit the present invention. Unless otherwise specified, all raw materials and reagents in the present invention are raw materials and reagents from the conventional market.
[0089] Preparation of photovoltaic panels
[0090] Example 1
[0091] 1) Preparation of cellulose nanocrystal grafted with phytic acid melamine (CNC-PA-MEL): Nanocellulose was dispersed in water, and then a phytic acid aqueous solution was added, and an acidic catalyst was added, and the pH value of the solution was adjusted to 3, and the reaction was carried out at 120°C for 8 hours. After the reaction, the solution was repeatedly centrifuged and washed 10 times with a large amount of deionized water; then the nanocellulose grafted with phytic acid was dispersed in water, and a melamine aqueous solution was added, and the reaction was carried out at 120°C for 8 hours. After the reaction was completed, the solution was repeatedly centrifuged and washed 10 times with a large amount of deionized water, and freeze-dried to obtain a nanocellulose-based flame retardant, wherein the mass ratio of nanocellulose: phytic acid: melamine was 1:5:5;
[0092] 2) adding 1.5 parts of ultraviolet absorber (UV-1577), 2 parts of benzoyl peroxide (BPO), 5 parts of vinyl polydimethylsiloxane (PDSV) and 1.5 parts of polycarbodiimide (PCD) to 80 parts of methyl methacrylate (MMA) by weight, and stirring and mixing them evenly, wherein the molecular weight of PDSV is 10000 (PDSV-10000);
[0093] 3) adding 10 parts of cellulose nanocrystal grafted melamine phytate (CNC-PA-MEL) particles to the mixture obtained in step 1), and stirring for 10 minutes to make it evenly dispersed;
[0094] 4) vacuuming and degassing the mixture;
[0095] 5) After removing the bubbles, pour the mixture into the mold until the resin fills the entire mold, and put it into an oven for curing. The curing process is divided into three stages. The curing temperature of the first stage is 90°C and the curing time is 25 minutes; the curing temperature of the second stage is 60°C and the curing time is 60 minutes; the curing temperature of the third stage is 120°C and the curing time is 60 minutes;
[0096] 6) After curing and molding, the sheet is taken out from the mold to obtain a new flame-retardant and lightweight photovoltaic sheet.
[0097] Example 2
[0098] The difference between Example 2 and Example 1 is that the addition amount of CNC-PA-MEL is adjusted to 1 part.
[0099] Example 3
[0100] The difference between Example 3 and Example 1 is that the addition amount of CNC-PA-MEL is adjusted to 5 parts.
[0101] Example 4
[0102] The difference between Example 4 and Example 1 is that the molecular weight of the PDSV used is 2000 (ie, PDSV-2000).
[0103] Example 5
[0104] The difference between Example 5 and Example 1 is that the molecular weight of the PDSV used is 6000 (PDSV-6000).
[0105] Example 6
[0106] The difference between Example 6 and Example 1 is that the added amount of UV-1577 is adjusted to 0.5 parts.
[0107] Comparative Example 1
[0108] The difference between Comparative Example 1 and Example 1 is that CNC-PA-MEL is not added in Comparative Example 1.
[0109] Comparative Example 2
[0110] The difference between Comparative Example 2 and Example 1 is that the added amount of CNC-PA-MEL in Comparative Example 2 is 15 parts.
[0111] Comparative Example 3
[0112] The difference between Comparative Example 3 and Example 1 is that PDSV is not added in Comparative Example 3.
[0113] Comparative Example 4
[0114] The difference between Comparative Example 4 and Example 1 is that UV-1577 is not added in Comparative Example 4.
[0115] Comparative Example 5
[0116] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, no PCD is added.
[0117] Photovoltaic panel performance test:
[0118] The photovoltaic panel products prepared in the above embodiments and comparative examples were subjected to impact strength test, light transmittance test, PCT accelerated aging test, heat deformation temperature test, wear resistance test and flame retardancy test in sequence. The test results are shown in Table 1.
[0119] The performance test method of photovoltaic panels is as follows:
[0120] Impact strength test: Tested according to GB / T 1043.1-2008 standard.
[0121] Light transmittance test: Tested according to GB / T 2410-2008 standard.
[0122] PCT accelerated aging test: Tested according to JESD22-A102-C standard.
[0123] Heat deformation temperature test: Tested according to GB / T 1634-2004 standard.
[0124] Abrasion resistance test: Tested according to FLTM BO 162-01 standard.
[0125] Flame retardant test: Tested according to GB / T8624-2012 standard.
[0126]
[0127] It can be seen from Examples 1-3 in Table 1 that the more CNC-PA-MEL is added, the better the impact resistance, heat resistance and wear resistance of the photovoltaic panel are.
[0128] It can be seen from Comparative Example 1 in Table 1 that without adding CNC-PA-MEL, the photovoltaic panel does not have flame retardant properties. This is because CNC-PA-MEL nanoparticles are easily dispersed in the PMMA matrix and have a certain reinforcing effect on PMMA. At the same time, CNC-PA-MEL is also a flame retardant that can improve the flame retardant properties of PMMA.
[0129] It can be seen from Comparative Example 2 in Table 1 that when the addition amount of CNC-PA-MEL is 15 parts, the impact resistance, light transmittance, heat resistance and wear resistance all decrease. This is because excessive CNC-PA-MEL nanoparticles will agglomerate in PMMA, resulting in reduced performance of the photovoltaic panel.
[0130] It can be seen from Examples 1, 4, 5 and Comparative Example 3 in Table 1 that the addition of PDSV can greatly improve the impact resistance, PCT48h aging performance, heat resistance and wear resistance of the sheet, and as the molecular weight of PDSV increases, the performance of the sheet becomes better. This is because under the action of the initiator, the molecules of MMA and PDSV can cross-link and solidify to form a network structure. The formation of the network structure will increase the rigidity of the material, improve the wear resistance, make it difficult for the molecular chain segments to move, and improve the heat resistance of the sheet; at the same time, the PDSV material contains polysiloxane molecular chains, which have a low surface tension and can effectively reduce the friction coefficient of the PMMA surface, further improving the wear resistance and scratch resistance of PMMA.
[0131] It can be seen from Examples 1, 6 and Comparative Example 4 in Table 1 that the addition of UV-1577 can significantly improve the UV yellowing resistance of the board, and as the amount of UV-1577 added increases, the UV yellowing resistance is further improved.
[0132] It can be seen from Example 1 and Comparative Example 5 in Table 1 that the addition of PCD can improve the yellowing resistance of PCT 48h.
[0133] Therefore, the comprehensive performance of Example 1 in this application is the best.
Claims
1. A photovoltaic panel, wherein: The raw materials for preparing the photovoltaic plate include: methyl methacrylate and nanocellulose-based flame retardant. The nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or its derivatives.
2. The photovoltaic panel according to claim 1, wherein: The raw materials for preparing the photovoltaic plate also include: an initiator, an anti-hydrolysis agent, an ultraviolet absorber, and / or an anti-scratch agent.
3. The photovoltaic panel according to claim 2, wherein: In terms of weight, the raw materials for preparing the photovoltaic panel include: 75-95 parts of methyl methacrylate, 1-10 parts of the nanocellulose-based flame retardant, 0.5-2 parts of the ultraviolet absorber, 1-5 parts of the scratch-resistant agent, 1-3 parts of the initiator, and 0.5-5 parts of the anti-hydrolysis agent.
4. The photovoltaic panel according to any one of claims 1 to 3, wherein: The degree of substitution of the nanocellulose-based flame retardant is 30%-70%.
5. The photovoltaic panel according to any one of claims 1 to 4, wherein: The organic acid containing a phosphoric acid group is phytic acid and / or polyphosphoric acid.
6. The photovoltaic panel according to any one of claims 1 to 5, wherein: The nanocellulose-based flame retardant is nanocellulose grafted with phytic acid melamine, such as a combination of one or more of bacterial nanocellulose grafted with phytic acid melamine, microfiber nanocellulose grafted with phytic acid melamine and cellulose nanocrystal grafted with phytic acid melamine; preferably, the initiator is a combination of one or more of tert-butyl perbenzoate (TBPB), benzoyl peroxide (BPO) and azobisisobutyl cyanide (AIBN); preferably, the anti-hydrolysis agent is polycarbodiimide (PCD), isocyanates and Preferably, the ultraviolet absorber is a combination of one or more of 2-(2H-benzotriazole-2-yl)-6-dodecyl-4-methylphenol (UV-571), 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (UV-P), 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)benzotriazole (UV-328) and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol (UV-1577); Preferably, the scratch resistant agent is an organic compound containing a polysiloxane molecular chain and an unsaturated bond, preferably, the molecular weight of the scratch resistant agent is 2000-10000, preferably, the scratch resistant agent is vinyl polydimethylsiloxane (PDSV).
7. A method for preparing the photovoltaic plate according to any one of claims 1 to 6, wherein: The method comprises: 1) adding a nanocellulose-based flame retardant to methyl methacrylate or a mixture containing methyl methacrylate and mixing them uniformly, wherein the nanocellulose-based flame retardant is formed by grafting nanocellulose with an organic acid containing a phosphoric acid group and melamine or a derivative thereof; 2) Degassing the mixture obtained in step 1) and curing it to obtain the photovoltaic panel.
8. The method according to claim 7, wherein: The mixture containing methyl methacrylate further contains: an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber.
9. The method according to claim 7, wherein: In step 1), after the nanocellulose-based flame retardant is added to methyl methacrylate and mixed evenly, an initiator, an anti-hydrolysis agent, an anti-scratch agent, and / or an ultraviolet absorber are added and mixed evenly.
10. The method according to any one of claims 7 to 9, wherein: The nanocellulose-based flame retardant is obtained by first reacting the nanocellulose with the organic acid containing a phosphoric acid group, and then reacting with the melamine or its derivative.
11. A photovoltaic module, wherein: The photovoltaic module includes a stacked front panel, solar cells and a back panel, wherein the solar cells are located between the front panel and the back panel, and at least one of the front panel and the back panel is made of a photovoltaic panel according to any one of claims 1-6 or a photovoltaic panel prepared by the method according to any one of claims 7-10.
Citation Information
Cited By
Coated photovoltaic glass and preparation method thereof
CN120441203A